Maternal Consumption of Sugar-Sweetened Beverages and Juices in Lactation Predicts Poorer Infant Neurodevelopment at 24 Postnatal Months. (29th May 2020) - Berger, Paige; Plows, Jasmine; Jones, Roshonda; Alderete, Tanya; Rios, Claudia; Poulsen, Marie; Fields, David; Bode, Lars; Peterson, Bradley; Goran, Michael
Abstract: Objectives: Our prior studies have shown that maternal sugar-sweetened beverage and juice (SSBJ) consumption influenced breast milk fructose, and higher breast milk fructose was associated with greater infant growth. It is unknown whether maternal SSBJ consumption in lactation also influences infant neurodevelopment. The aim of this study was to determine whether maternal SSBJ consumption in lactation was associated with infant cognitive, language, and motor development at 24 postnatal months. Associations of maternal fructose, added, and total sugar consumption with infant neurodevelopmental outcomes were also examined. Methods: Hispanic mother-infant pairs (N = 89) were recruited across the spectrum of pre-pregnancy BMI. Mothers completed two 24-hour dietary recalls at 1 and 6 postnatal months. The Bayley-III Scales were administered to all infants at 24 postnatal months to assess cognitive, language, and motor development. Multiple linear regressions were used to assess the correlations of maternal diet with infant Bayley-III outcomes, adjusting for maternal age, BMI, education level, energy intake, infant age, sex, and birthweight. Results: At 1 postnatal month, mothers consumed 2.7 ± 3.1 servings SSBJ, 22 ± 12 g fructose, 59 ± 35 g added sugar, and 98 ± 47 g total sugar per day, and all were inversely associated with infant Bayley-III outcomes. Every 1 serving increase in SSBJs was associated with a 0.24 decrease in cognitive, 0.50 decrease in language, and 0.43 decrease in motor development scores (all P's ≤0.01). At 6 postnatal months, maternal SSBJ consumption remained inversely associated with infant motor development scores (B = −0.24, P  = 0.03), but maternal fructose, added, and total sugar consumption were not associated with infant Bayley-III outcomes. Conclusions: Our findings suggest that maternal SSBJ consumption in early lactation is an adverse influence of infant neurodevelopmental outcomes at 24 postnatal months. Funding Sources: National Institute of Diabetes and Digestive and Kidney Diseases (NIH R01 DK110793); The Gerber Foundation (15PN-013).